PERANAN SEKOLAH DALAM MENSOSIALISASIKAN TATA TERTIB SISWA DI MTS MATHLA’UL ANWAR PONTIANAK - yarso, Meriyanti; Khosmas, F.Y.; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to reveal how the role of school in socializing students’ discipline in the Mathla’ul Mts Pontianak. This approach used qualitative with descriptive methods. The technique of data collection were observation, interview, and documentation. The resources in these study were primery and secondary data The research finding showed that the way of school to introduced students’ descipline. There were implementations school of regulation, divided school of regulations, and indexes students’ mistake which is shared all new students in during Students’ Orientation Period (MOS). Therefore, there ware the monitoring activities for students and revised the implemetations, machanism, or contents of school regulattions that did in the teacher council meeting. Whereas the action which was against regulation were get consequences by students did. Procedure of consequences which have obtained 1-10 indexes. It was get an admonition. 21-30 indexes, the parents were call and make the first statement letter, 31-40 indexes it was call for parents and made a third statement, if more than 40 so the students will be rentruned to parents/ expelled from school. Keywords: Regulations, Roles of school, Socialization